Clostridium butyricum Induces the Production and Glycosylation of Mucins in HT-29 Cells - Lili, Qi; Xiaohui, Lu; Haiguang, Mao; Jinbo, Wang (Frontiers in Cellular and Infection Microbiology, 2021)
C. butyricum is a common gut commensal bacterium, which has many positive functions in human intestine. In this study, we investigated the effects of monosaccharide and its derivatives on the adhesion of C. butyricum to the mucus of HT-29 cells. RNA interference was performed to assess the roles of MUC2 and glycan in the adhesion of C. butyricum to HT-29 cells. The effects of C. butyricum on the glycosylation of mucins were assayed with fluorescence microscope. The expression levels of mucins and glycotransferases were also determined. The results showed that C. butyricum could adhere to the mucins secreted by HT-29 cells. Several kinds of monosaccharides inhibited the adhesion of C. butyricum to HT-29 cells, which suggested that the mucus glycan was the attaching sites of this bacterium. Knockdown of MUC2, FUT2 or GALNT7 significantly decreased the numbers of the bacteria adhering to HT-29 cells. When colonizing on the surface of HT-29 cells, C. butyricum could increase the production of mucins, promote the expression of glycotransferase, and induce the glycosylation of mucins. These results demonstrated that the glycan of mucus played important roles in the adhesion of C. butyricum to HT-29 cells. This study indicates for the first time that C. butyricum possesses the ability to modulate the glycosylation profile of mucus secreted by HT-29 cells. These findings contribute to understanding the mechanism of interaction between colonic epithelial cells and commensal bacteria.